PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII2 SMP NEGERI 13 PEKANBARU - Ade Rozalinda; Zuhri Zuhri; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve learning process and increase student’smathematical achievement through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle. The research was conducted in class VIII2 SMP Negeri 13 Pekanbaru in the second semester of the 2018/2019 academic year. The subject of this research consist of 40 students, there are 29 girls and 11 boys. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the Syllabus, Lesson Plan and Activity Sheets. Instrument data collectors used in this research are observation sheet and mathematical achievement test. Application of PBL model also gives positive impact on the implementation of learning process that students become more active in learning activities so that learning is not centered on the teacher. Students are also trained to build their own knowledge and can find their own mathematical concepts through the presentation of problems close to the student's real life. The percentage of students which ispass Minimum Mastery Crieria (MMC) increase from 45% to 65% at the first test and to 80% at the second test. This research concludes that the implementation of PBL improved the learning process and the student’s mathematical achievement atclass VIII2 SMP Negeri 13 Pekanbaru in the second semester of the 2018/2019 academic year.Key Words: Classroom Action Research, Problem Based Learning models, Learning outcomes